A Triphenylphosphonium Functionalized AIE Conjugated Macrocyclic Tetramaleimide for Mitochondrial‐targeting Bioimaging. Issue 1 (28th November 2021) - Zeng, Wei; Lin, Mao‐Hua; Zhu, Ling‐Yun; Lin, Mei‐Jin
Comprehensive Summary: Development of subcellular organelle‐targeted bioimaging probes is of great importance in the field of early detection of diseases and exploring the behaviors of subcellular organelles. Herein, we present a triphenylphosphonium functionalized conjugated macrocyclic tetramaleimide (TPP‐CMT) as a mitochondrial‐targeting bioimaging probe. The core of TPP‐CMT is obtained by connecting two pyrenes and two benzenes through four maleimides. This unique structure endows TPP‐CMT with exceptional far red/near‐infrared aggregation‐induced emission (FR/NIR‐AIE) characteristics. TPP‐CMT is an excellent fluorescent emitter in most solvents and even in solid states. The quantum yield of TPP‐CMT was higher than 27% when dissolved in common middle‐polarity organic solvent and this value remained at 28.2% in its solid state. The introduction of four triphenylphosphonium on maleimide positions endows TPP‐CMT with mitochondrial‐targeting ability. Thanks to the FR/NIR‐AIE characteristics and the mitochondrial‐targeting ability, this well‐designed fluorescent probe was successfully employed for mitochondrial targeting bioimaging of HeLa and HepG2 cells. Abstract : A triphenylphosphonium functionalized conjugated macrocyclic tetramaleimide (TPP‐CMT) with FR/NIR‐AIE characteristics and mitochondrial‐ targeting ability has been developed and its mitochondrial targeting bioimaging has been conducted.